Assessment of the functional impact of foot involvement in patients with rheumatoid arthritis. (September 2022) - Fazaa, Alia; Triki, Wafa; Ouenniche, Kmar; Sellami, Meriem; Miladi, Saoussen; Souabni, Leila; Kassab, Selma; Chekili, Selma; Abdelghani, Kawther Ben; Laatar, Ahmed
Highlights: The assessment of the functional impact of the involvement of the feet during rheumatoid arthritis is relevant given that it is common in this chronic inflammatory rheumatism and that it can affect the functional prognosis of patients. To assess the functional impact, we used a validated self-questionnaire with good reproducibility and easily understandable by our patients: the Functional Foot Index (FFI). Due to the high frequency of foot involvement and its significant functional impact, meticulous examination of the feet and assessment of their functional impact must be one of the parameters for monitoring the disease. A better understanding of the peculiarities of the rheumatoid foot and the factors predicting its functional impact would optimize the care of patients with RA and thus improve their quality of life. Abstract: Aim of the work: We aimed to evaluate the impact of foot involvement in patients with rheumatoid arthritis (RA) using the functional foot index (FFI) and to identify predictive factors of the functional impact of foot abnormalities in RA patients. Patients and methods: This was a cross-sectional study including patients with RA meeting the criteria of the American College of Rheumatology and the European League Against Rheumatism 2010. The main epidemiological data, results of podoscopic and clinical examination of the foot and ankle, biological tests and radiological findings were collected. The presence of foot pain was assessed by a visual analogic scale (0–10), and the functional impact of foot involvement was assessed based on the validated French version of the FFI. Results: Fifty RA patients with an average age of 59.3 ± 9.9 years [39–79] were included, and 80% of them had foot involvement. Foot pain was present in 32 patients (64%), most frequently situated in the forefoot (56%). The average FFI score was 33.67 ± 30.53 [0–92.67]. The following factors had a significant association with the FFI score: an occupation soliciting the feet (p = 0.001), disease duration (p = 0.033, r = 0, 302), the Health Assessment Questionnaire (p = 0.0001, r = 0, 480), body mass index (p = 0.0001, r = 0, 654), the presence of podiatric abnormalities (p = 0.0001) and Visual Analog Scale foot pain (p = 0.0001, r = 0, 854). A significant association was also found between the FFI score and the presence of a hallux valgus (p = 0.004), a spread of the forefoot (p = 0.029), a claw of the toes (p = 0.002), a triangular forefoot (p = 0.0001), a quintus varus (p = 0.002), flat feet (p = 0.0001) and a valgus of the hindfoot (p = 0.001). Conclusion: Due to the high frequency of foot involvement and its significant functional impact, meticulous examination of the feet and assessment of their functional impact must be one of the parameters for monitoring the disease. Its impact on one's quality of life can be important. Level of clinical evidence: 4 (cohort studies, non experimental, observational studies).